CLINICAL IMPACTS OF BURNOUT SYNDROME AMONG ANESTHESIOLOGY RESIDENTS: AN OBSERVATIONAL STUDY - Tantri, Aida; Sugiarto, Adhrie; Mufaza, Uyun (Universitas Gadjah Mada, 2023)
Background: Anesthesiology residents have enormous responsibilities and pressure in the workplace that could lead to burnout syndrome. Burnout can be categorized into emotional exhaustion, depersonalization, and reduced personal accomplishment dimension. Burnout can affect clinical performance and patients' safety. This study examined the relationship between burnout level and clinical performance in anesthesiology residents.Methods: This was a prospective analytic observational study with a cross-sectional design. The sample size was estimated using the analytical hypothesis test formula with an unpaired numerical measurement scale and an estimated dropout of 10%. Burnout level was determined using Maslach Burnout Inventory and negative clinical performance was measured with the Anesthesiology Residents' Self-Reported Errors and Quality of Care Questionnaire. Data were analyzed using chi-square and unpaired T-Test.Results: Nineteen subjects (34.5%) suffered from moderate-high burnout levels in the emotional exhaustion dimension. In the depersonalization dimension, 51 subjects (92,7%) suffered from a moderate-high burnout level, and in the reduced personal accomplishment dimension, 28 subjects (50,9%) suffered from a moderate-high burnout level. Mean negative clinical performance scores in subjects with moderate and high burnout level were significantly different from subjects with none and low burnout subjects (26.86 ± 3.63 vs 28.79 ± 2.58, p = 0.045).Conclusion: Burnout was highly prevalent among anesthesiology residents. In anesthesiology residents, moderate and high burnout levels were significantly correlated with negative clinical performance scores.